Collaborating network in managing post the Mount Merapi’s disruption, Indonesia - Pratama, Prawira Yudha (Jamba, 2020)
Collaborative governance and social capital can help to form a resilient community in the wake of a disaster, such as the eruptions of Mount Merapi in Indonesia. This study examines the successfulness of the handling of disasters in Indonesia, with particular focus on eruptions of Mount Merapi. Disasters foster a close relationship between the government and the community in response to the emergency. This study uses a mixed method to analyse social networks in evaluating the structure of disaster networks in Indonesia and their implications for disaster management. Data were collected via a survey of 100 respondents from 28 institutions representing, for practical purposes, each population identified by each institution (government, non-governmental organisations and volunteers) that participated in handling the Merapi eruption disaster. The findings revealed that considerable miscommunication between institutions reduced the effectiveness of disaster management so that close discussion about conflict resolution was needed to develop more mature and systematic planning. Inter-agency trust is also felt to be necessary in disaster management. Trust between agency members and other institutions strongly supports the success of systematic disaster management. Meanwhile, every institution must foster open leadership by giving individuals with precise knowledge of the situation and the condition of the disaster area a mandate to lead directly in the field. Disaster governance is carried out through the agreement of each institution formed in the Disaster Emergency Planning (Rencana Penanggulangan Kedaruratan Bencana – RPKB) guidelines. These guidelines expect the Government and the community to coordinate with each other in a structured and systematic manner in the process of disaster management.